Between Bone and Epithelium: A rare case of Adamantinoma - Dhakal, Smriti; Bhattarai, Shaswat; Pandey, Greta; Bastakoti, Shankar (Annapurna Journal of Health Sciences, 2026)
Adamantinoma is a rare, low-grade malignant bone tumor that most commonly affects the tibial diaphysis. Due to its nonspecific clinical and radiologic presentation, diagnosis can be challenging. Immunohistochemistry plays an important role in confirming the diagnosis. We report a case of a 38-year-old woman who presented with a one-year history of gradually progressive swelling and pain in the right leg. Imaging revealed a suspicious malignant lesion in the mid-tibia. Initial biopsy suggested a malignant mesenchymal neoplasm with a differential diagnosis of synovial sarcoma. Immunohistochemical analysis demonstrated positivity for CK, p63, p40, CK5/6, vimentin and D2-40, confirming the diagnosis of spindle cell variant of adamantinoma.